2021
DOI: 10.14745/ccdr.v47i10a02
|View full text |Cite
|
Sign up to set email alerts
|

National Influenza Annual Report, Canada, 2020–2021, in the global context

Abstract: During the 2020–2021 Canadian influenza season, no community circulation of influenza occurred. Only 69 positive detections of influenza were reported, and influenza percent positivity did not exceed 0.1%. Influenza indicators were at historical lows compared with the previous six seasons, with no laboratory-confirmed influenza outbreaks or severe outcomes being reported by any of the provinces and territories. Globally, influenza circulation was at historically low levels in both the Northern and the Southern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…Lastly, the COVID-19 pandemic changed the influenza landscape and demonstrated the ongoing the importance of routine vaccination. During the 2020/2021 influenza season, Canada reported no community circulation of influenza [46], and a markedly lower number of influenza cases were reported compared to previous seasons despite an increased number of influenza tests performed [47]. Despite this initial decrease in cases during the SARS-CoV-2 pandemic, in the 2021/2022 Canadian season, influenza activity and related healthcare visits rose [46,48], and the vaccination coverage of groups at high risk of severe outcomes in 2020-2021 was similar to that of the prior influenza season [46].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, the COVID-19 pandemic changed the influenza landscape and demonstrated the ongoing the importance of routine vaccination. During the 2020/2021 influenza season, Canada reported no community circulation of influenza [46], and a markedly lower number of influenza cases were reported compared to previous seasons despite an increased number of influenza tests performed [47]. Despite this initial decrease in cases during the SARS-CoV-2 pandemic, in the 2021/2022 Canadian season, influenza activity and related healthcare visits rose [46,48], and the vaccination coverage of groups at high risk of severe outcomes in 2020-2021 was similar to that of the prior influenza season [46].…”
Section: Plos Onementioning
confidence: 99%
“…During the 2020/2021 influenza season, Canada reported no community circulation of influenza [46], and a markedly lower number of influenza cases were reported compared to previous seasons despite an increased number of influenza tests performed [47]. Despite this initial decrease in cases during the SARS-CoV-2 pandemic, in the 2021/2022 Canadian season, influenza activity and related healthcare visits rose [46,48], and the vaccination coverage of groups at high risk of severe outcomes in 2020-2021 was similar to that of the prior influenza season [46]. As influenza seasons during the SARS-CoV-2 pandemic begin to regain their typical severity and frequency of infection and as influenza vaccination has plateaued in groups at high risk of severe outcomes, it remains critical to continue investigating patterns of influenza vaccination uptake, especially among groups at high risk of severe outcomes.…”
Section: Plos Onementioning
confidence: 99%
“…However, since the emergence of SARS-CoV-2, epidemiologic studies have demonstrated that the number of influenza cases has decreased markedly in the Northern and Southern Hemispheres [4][5][6][7], whereas RSV activity occurred at an unusual time [8][9][10]. For the 2020-2021 season, only 69 influenza cases were reported in Canada, which was lower than the average of 52,169 influenza detections recorded during the past six seasons [11]. Regarding RSV, only 986 cases were detected in Canada for the 2020-2021 season, which was around 20 times lower than the 18,916 cases reported during the 2019-2020 season [12].…”
Section: Introductionmentioning
confidence: 95%
“…Infections with these viruses were at a historic low. This is likely due to the low rates of these viruses circulating in the general population as a result of increased public health safety measures such as increased hand-washing, physical distancing, mask use, decreased contacts and higher influenza vaccine coverage [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%